2023
DOI: 10.20944/preprints202307.2138.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scrub Typhus: Epidemiology, Clinical Presentations, and Diagnostic Approaches

Ramendra Pati Pandey,
M Beyau Konyak,
Monika Soni
et al.

Abstract: Scrub typhus (ST) is one of the most neglected tropical diseases, a leading cause of acute undifferentiated febrile illness in areas of the ‘tsutsugamushi triangle’, diagnosed frequently in South Asian countries. The bacteria Orientia tsutsugamushi is the causative agent of the disease, which enters to human body through the bite of trombiculid mite (Chigger) of the genus Leptotrombidium deliense.The diagnosis of the disease becomes challenging as its early symptoms mimic other febrile illn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
0
0
Order By: Relevance
“…Narang et al found scrub typhus affecting 15.89% of the population in 2023, with a higher prevalence among individuals aged 41-60, females, and farm workers, particularly during monsoon and post-monsoon seasons[22]. Pandey et al highlighted a significant number of cases in Eastern India, especially Nagaland and Manipur[23]. Devamani et al conducted a study in south India, in the Tamil Nadu districts of Vellore, Thiruvannamalai, and Salem, and recruited 1,353 individuals from 15 peri-forest hill villages, 17 rural plain villages, and 16 urban communities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Narang et al found scrub typhus affecting 15.89% of the population in 2023, with a higher prevalence among individuals aged 41-60, females, and farm workers, particularly during monsoon and post-monsoon seasons[22]. Pandey et al highlighted a significant number of cases in Eastern India, especially Nagaland and Manipur[23]. Devamani et al conducted a study in south India, in the Tamil Nadu districts of Vellore, Thiruvannamalai, and Salem, and recruited 1,353 individuals from 15 peri-forest hill villages, 17 rural plain villages, and 16 urban communities.…”
mentioning
confidence: 99%
“…Narang et al observed 15.80% prevalence, with higher rates in the 41-60 year age group, in females, and among farm workers during monsoon seasons[22]. In the study in Northeast India byPandey et al, 55.5% of cases were primarily from Nagaland and Manipur, with a 2.4% case fatality rate[23]. Damodar et al linked scrub typhus to AES in south Indian states[25].…”
mentioning
confidence: 99%